Auditory grouping mechanisms reflect a sound's relative position in a sequence - Hill, Kevin T.; Bishop, Christopher W.; Miller, Lee M. (Frontiers in Human Neuroscience, 2012)
The human brain uses acoustic cues to decompose complex auditory scenes into its components. For instance to improve communication, a listener can select an individual “stream”, such as a talker in a crowded room, based on cues such as pitch or location. Despite numerous investigations into auditory streaming, few have demonstrated clear correlates of perception; instead, in many studies perception covaries with changes in physical stimulus properties (e.g. frequency separation). In the current report, we employ a classic ABA streaming paradigm and human electroencephalography (EEG) to disentangle the individual contributions of stimulus properties from changes in auditory perception. We find that changes in perceptual state – that is the perception of one versus two auditory streams with physically identical stimuli – and changes in physical stimulus properties are reflected independently in the event-related potential (ERP) during overlapping time windows. These findings emphasize the necessity of controlling for stimulus properties when studying perceptual effects of streaming. Furthermore, the independence of the perceptual effect from stimulus properties suggests the neural correlates of streaming reflect a tone’s relative position within a larger sequence (1st, 2nd, 3rd) rather than its acoustics. By clarifying the role of stimulus attributes along with perceptual changes, this study helps explain precisely how the brain is able to distinguish a sound source of interest in an auditory scene.